All Days 2012
DOI: 10.2118/151062-ms
|View full text |Cite
|
Sign up to set email alerts
|

A New Emulsified Acid to Stimulate Deep Wells In Carbonate Reservoirs: Coreflood and Acid Reaction Studies

Abstract: Acid treatments in high temperature deep wells drilled in carbonate reservoirs represent a challenge to the oil industry. The high temperature of deep wells requires a special formulation of emulsified acid that can be stable and effective at such high temperatures. At these high temperatures, both the reaction rate between acid and rock, and corrosion rate of tubulars are high. This fact makes protection of tubulars and reducing the reaction rate between rock and acid challenging. A new emulsif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The most commonly used ratio for the two phases is a 70:30 acid to oil ratio. 161 Diesel emulsified acid (DEA) is common as it gains viscosity while shearing and can divert itself to low permeability formation sections. Nevertheless, it usually requires a long mixing time and could result in high-pressure losses during injection.…”
Section: Application Of Nps In Emulsion-based Stimulationmentioning
confidence: 99%
“…The most commonly used ratio for the two phases is a 70:30 acid to oil ratio. 161 Diesel emulsified acid (DEA) is common as it gains viscosity while shearing and can divert itself to low permeability formation sections. Nevertheless, it usually requires a long mixing time and could result in high-pressure losses during injection.…”
Section: Application Of Nps In Emulsion-based Stimulationmentioning
confidence: 99%
“…and Chan, 2004 ), and the fracturing fluid technique has received considerable attention. Subsequently, other fracturing fluid techniques were greatly developed, for example, hydraulic fracturing fluids ( Zhang et al, 2018a ; Zhou et al, 2019 ), oil-based fracturing fluid ( Zhang et al, 2018b ), emulsified fracturing fluid ( Buijse and van Domelen, 2000 ; Sayed et al, 2012 ; Zakaria and Nasr-EI-Din, 2015 ), foam fracturing fluid ( Sayed and Al-Muntasheri, 2016 ; Dehdari et al, 2020 ; Qu et al, 2020 ), thickening fracturing fluid ( Liu and Li, 2016 ; Cai et al, 2018 ), alcohol-based hydraulic fracturing ( Marrugo-Hernandez et al, 2018 ), and surfactant fracturing fluid ( Zhang et al, 2018c ; Lu et al, 2019 ; Mejia et al, 2019 ; Tangirala and Sheng, 2019 ; Zhang et al, 2019 ). Although hydraulic fracturing fluid has been widely used, it still represents the poor stability to shear resistance and serious filtration loss.…”
Section: Introductionmentioning
confidence: 99%
“…Buijse and van Domelen studied the effect of the injection rate, viscosity, and acid volume fraction on the emulsified acid pore volume to breakthrough in carbonate rocks. Sayed et al studied the performance of the emulsified acid in low and high permeability carbonate formations using coreflood experiments. It was found that the high permeability carbonate cores consumed more acid volume to breakthrough than did the low permeability cores.…”
Section: Introductionmentioning
confidence: 99%